PERLINDUNGAN HUKUM WANPRESTASI PEMOTONGAN GAJI TERLALU BESAR OLEH P3MI TERHADAP PEKERJA MIGRAN INDONESIA - Irma Abidahsari (2024)
It becomes an urgency which occupies a leading position on the provision of legal protection for the injured party in the default of the other party. The purpose of the research is to find out how the form of default of the Indonesian migrant worker placement company PT X to Indonesian migrant workers and to find out the form of legal protection of Indonesian migrant workers due to default of the Indonesian Migrant Worker Placement Company PT X. By using normative legal research methods through a statutory approach and case approach. The results of the study found that the form of default of the Indonesian migrant worker placement company PT X to Indonesian migrant workers is doing what was promised but not as promised. Where, P3MI PT X has the obligation to carry out salary deductions as a form of reimbursement of placement costs from borrowing money by Mrs. S, but the act of deducting the salary turns out to be more than what should be stated in the agreement "Statement of Costs and Salaries." As well as, the form of legal protection for Indonesian migrant workers due to the default of the Indonesian Migrant Worker Placement Company PT X includes preventive through regulations in Article 1246 of the Civil Code and other related laws and repressive when the case has occurred through mediation and / or consensus deliberation, based on the Legal System Theory by Lawrence Meir Friedman, namely Structure, Substance and Legal Culture. BP3MI DKI Jakarta as a legal structure, acts as a mediator officer who plays an important role as an arbiter and resolves what is the will of the two parties by mutual consent, with the final agreement in the form of compensation to the aggrieved Indonesian Migrant Worker in the amount of ten million rupiah.